Mortality and clinical outcomes of Vancouver type B periprosthetic femoral fractures <subtitle>a multicentre retrospective study</subtitle> - Hideomi Takami; Yasuhiko Takegami; Katsuhiro Tokutake; Hiroshi Kurokawa; Manato Iwata; Satoshi Terasawa; Takeshi Oguchi; Shiro Imagama (Bone & Joint Open, 2023)
AimsThe objectives of this study were to investigate the patient characteristics and mortality of Vancouver type B periprosthetic femoral fractures (PFF) subgroups divided into two groups according to femoral component stability and to compare postoperative clinical outcomes according to treatment in Vancouver type B2 and B3 fractures.MethodsA total of 126 Vancouver type B fractures were analyzed from 2010 to 2019 in 11 associated centres' database (named TRON). We divided the patients into two Vancouver type B subtypes according to implant stability. Patient demographics and functional scores were assessed in the Vancouver type B subtypes. We estimated the mortality according to various patient characteristics and clinical outcomes between the open reduction internal fixation (ORIF) and revision arthroplasty (revision) groups in patients with unstable subtype.ResultsThe one-year mortality rate of the stable and unstable subtype of Vancouver type B was 9.4% and 16.4%. Patient demographic factors, including residential status and pre-injury mobility were associated with mortality. There was no significant difference in mortality between patients treated with ORIF and Revision in either Vancouver B subtype. Patients treated with revision had significantly higher Parker Mobility Score (PMS) values (5.48 vs 3.43; p = 0.00461) and a significantly lower visual analogue scale (VAS) values (1.06 vs 1.94; p = 0.0399) for pain than ORIF in the unstable subtype.ConclusionAmong patients with Vancouver type B fractures, frail patients, such as those with worse scores for residential status and pre-injury mobility, had a high mortality rate. There was no significant difference in mortality between patients treated with ORIF and those treated with revision. However, in the unstable subtype, the PMS and VAS values at the final follow-up examination were significantly better in patients who received revision. Based on postoperative activities of daily life, we therefore recommend evision in instances when either treatment option is feasible.Cite this article: Bone Jt Open 2023;4(1):38–46.